MEASURES TO PREVENT AGGRESSIVE ATTITUDES BY THE TEACHER TO THE STUDENT FOR LATING TO THE LESSONS - Shomurotov Ulugbek Melikboboyevich, Bashirova Sevara Suyun qizi, Sattorov Ravshan Tojiddinovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Punctuality is an important virtue that needs to be inculcated in students from a young age. Showing up to lessons on time allows for an orderly and productive learning environment in the classroom. However, there may be valid reasons beyond a student's control why they occasionally arrive late. In such situations, it is imperative that teachers respond with empathy, patience and compassion rather than aggression or harsh punishment. An aggressive attitude from an authority figure like a teacher can psychologically damage impressionable young minds and negatively impact the student teacher relationship. This article discusses some measures that can help prevent aggressive reactions from teachers when students are occasionally late to lessons.